Desarrollo de un alimento deshidratado tipo BARF para perros incorporando subproductos del faenamiento porcino - Párraga Rivera, María Rocío (2023)
The purpose of this research was to establish the percentages of by-products from pig slaughter and the dehydration conditions in the chemical and bromatological characteristics, microbiological quality and yield (%), in the development of a BARF-type food for dogs. The relation of viscera and industrial pork meat (60%) was made with the incorporation of vegetables (40%) under conditions of temperature-time of dehydration (50°C-5h, 60°C-4h and 70°C-3h). An A*B factorial arrangement was used in DCA, obtaining six treatments with three replicates. In the nutritional composition of the dehydrated BARF food, all the evaluated treatments comply with the nutritional (ash, fiber, moisture, fat and protein) requirements established by the AAFCO and the Ecuadorian Technical Regulation Rte Inen 187 (2014). However, T2 was chosen as the most suitable, evidencing 3.893% ash, 1.116% fiber, 11.940% moisture, 10.330% fat and 30.896% protein. The microbiological analysis reported that all the treatments were within the permissible parameters in molds, fungi and yeasts according to the SAG and FEDIAF. While in the determination of the percentage of mass yield, the treatments did not present a significant difference (p>0.05) and reported average values that ranged from 31.60% to 35.07% of yield.